Expression of Inducible Nitric Oxide Synthase in Keratocystic Odontogenic Tumour and Variants of Ameloblastoma – A Comparative Study - H, Diana (J Clin Diagn Res, 2014)
Introduction: The odontogenic keratocyst (OKC) is a histopathologiocally and behaviourally unique and specific entity. It is the most aggressive and recurrent of all the cysts and shows characteristics resembling both cyst and a tumour. The unique nature of OKC and the recent shift of OKC as a tumour made us evaluate yet another factor, Inducible nitric oxide synthase an (iNos) enzyme which has been implicated in the tumourigenesis of various neoplasms. Aims and Objects: The objective of the study was to analyse and compare the immunohistochemical expression of iNOS in odontogenic keratocysts (OKC’s) in variants of ameloblastoma affecting the oral cavity, to determine the neoplastic potential of OKC and to reinforce the classification of OKC as keratocystic odontogenic tumour. Materials and Methods: Thirty two specimens, eight specimens each in OKC, follicular ameloblastoma, plexiform ameloblastoma and unicystic ameloblastoma, taken from the Oral Pathology Department were randomly selected for this study and were evaluated for epithelial expression of iNOS by immunohistochemistry Results: Epithelial immunoreactivity to iNOS was strongly positive in 93.5% of follicular ameloblastomas, 68.7% of plexiform ameloblastomas, 66.9% of odontogenic keratocysts and 66.2% of unicystic ameloblastomas. Conclusion: iNOS may be an important marker involved in the biological behaviour of OKC. Furthermore the presence of increased expression of iNOS in Follicular ameloblastomas followed by Plexiform ameloblastomas, OKCs and Unicystic ameloblastomas is yet another evidence to support that OKC could be considered as a neoplasm.